The Differences in Effectiveness of Granting Thick Blankets and Heating Lamps in Sectio Caesarea Post-Surgery Patients who Undergo Hypothermia in the OK Recovery Room in Sanjiwani District Hospital Gianyar - Kesuma, I Gusti Bagus Intan Wijaya (Coping: Community of Publishing in Nursing, 2013)
Caesaria sectio surgery can cause postoperative incidence of hypothermia. Hypothermia can lead to decreased of organ function. Therefore, hypothermia must be addressed before causing further damage. Some handling of hypothermia can be done like a thick blanket provision and providing of heating lamps. However, the effectiveness of these methods has not been known yet. The aim of this study was to determine the differences in effectiveness of thick blankets provision and heating lamps in sectio Caesaria post-surgical patients who undergo hypothermia in the OK recovery room in Sanjiwani District Hospital Gianyar. The research plan used Pre-experimental, it was Intact-Group Comparison. Sampling technique used was nonprobability sampling that was Purposive sampling; it was obtained the sample of 32 respondents starting from May 9 until June 5, 2012. The data was collected by using observational techniques to determine the increase in temperature every five minutes. The results of 32 respondents were divided into two groups namely the group of thick blankets and the group of heating lamps. It was obtained that the average time in group of thick blanket was 65,9 minutes, while the average time in heating lamps group was 49,06 minutes. According to t-independent test showed that there were significant differences between thick blankets provision and heating lamps to overcome the incidence of hypothermia (p value = 0.000). Where it was discovered that heating lamp was more effective than a thick blanket to overcome the hypothermia. It was seen from the time average of each group.
Keywords: hypothermia, thick blankets, heating lamps